Avaliação da resistência ao deslocamento do MTA e MTA HP acrescidos de nanopartículas de clorexidina - Carmo, Patrícia Pimentel do (2017)
The aim of the present study was to evaluate the influence of the addition of 2% chlorhexidine nanoparticles, equivalent to 2% of the total weight of the material, on the displacement resistance of MTA and MTA HP (Angelus, Londrina, Brasil) endodontic repair cements in contact with dentin. The endodontic materials in their original formulation were used as reference for comparison. Fifteen human permanent upper central incisors were selected and two dentin slices (1 ± 0.1 mm thick) were obtained from the cementoenamel junction of each root. Two 0.8 mm diameter holes were made in each slice. The samples received standard irrigation and were dried with absorbent paper. Then, each of the holes was filled with the materials in their original formulation or the added chlorhexidine nanoparticle materials and the samples were stored in a humidified environment in phosphate-buffered saline (pH 7.2) for 7 days at 37°C . After storage, a push-out test was performed. The Kruskal-Wallis test and Mann Whitney test were used to evaluate the strength of dentin adhesion of the repair cements tested. The tests were submitted to the Bonferroni multiple correction test, with a significance level set at α = 5%. The results of the present study show that samples filled with MTA HP (MTA HP and MTA-HP-CHX) had the highest dentin bond strength values (p <0.05) when compared to MTA-filled samples (MTA and MTA- CHX). The incorporation of chlorhexidine nanoparticles did not influence the bond strength of the tested materials (p> 0.05). The present study allows to conclude that the incorporation of a nanoparticulated anti-microbial agent based on chlorhexidine did not affect the resistance to the displacement of the repair materials MTA and MTA-HP.